Estrutura de mercado e esforço tecnológico - Alves, Roberta Maitino de Oliveira (2007)
The relationship between market structure and technological innovation has been widely studied; however there is no literature’s consensus on how this relationship is shaped. An important attribute that makes the understanding of this relationship important is its possible influence on antitrust practices, considering that standard antitrust policy assumes that perfect competition is the best solution to maximize welfare. This dissertation investigates the impact of market concentration (measured as HHI index) on innovative activities expenditures for Brazilian industrial sectors. I test the hypothesis that competition influences firm’s internal R&D expenditures in an inverted U shape, as stated by Scherer and Ross (1989) and Aghion et al. (2002). Applying panel data analysis I find evidences that an inverted U shape exits and the HHI index that maximizes firm’s internal R&D expenditures is about 0.30. On the other hand, when specific industry effects are controlled, HHI index explanatory power decreases. Additionally I find evidences of negative relationship between competition and innovative expenditures for low risk innovative activities.